2020
DOI: 10.1186/s12889-020-09125-2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of institutional delivery service utilization in Ethiopia: a population based cross sectional study

Abstract: Background: The incidence of maternal mortality remains unacceptably high in developing countries. Ethiopia has developed many strategies to reduce maternal and child mortality by encouraging institutional delivery services. However, only one-fourth of women gave birth at health facility, in the country. This, this study aimed to identify individual level factors and to assess the regional variation of institutional delivery utilization in Ethiopia. Methods: Data were obtained from the 2016 Ethiopian demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
39
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 37 publications
18
39
1
Order By: Relevance
“…Furthermore, their autonomy to decide on place of delivery is better in educated women than non-educated ones. A similar nding was also observed in different studies conducted in Ethiopia [44,45] and Bangladish [48].…”
Section: Factors Associated With Institutional Deliverysupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, their autonomy to decide on place of delivery is better in educated women than non-educated ones. A similar nding was also observed in different studies conducted in Ethiopia [44,45] and Bangladish [48].…”
Section: Factors Associated With Institutional Deliverysupporting
confidence: 88%
“…Additionally, physical accessibility of health facility is better in urban than rural. The same nding was also observed in a national level study conducted in Ethiopia [44,45], lay Gayint district, Ethiopia[46], and studies conducted in Bangladish [47,48].…”
Section: Factors Associated With Institutional Deliverysupporting
confidence: 81%
“…This result is supported by other studies done in Ethiopia and abroad. 29,[39][40][41][42] Mothers whose age range from 18 to 25 years at first pregnancy were two times more likely to use health facility delivery as compared to those mothers whose age was less than 18 years of age. This finding is not supported by other local studies done in Ethiopia [43][44][45] and Nepal 46 which revealed that younger…”
mentioning
confidence: 99%
“…The increased log-likelihood and decreased deviance were an indication of good model fitness (Table 4). (13). There was a high variation from pocket studies but it showed good improvement from EDHS 2016.…”
Section: Ethiopia 2019mentioning
confidence: 97%
“…Family size, accessibility of transportation, planned pregnancy, information about the place of delivery, participation of women in monthly health conference (PWMHC), information about exempted service, and having antenatal care (ANC) follow up during their last pregnancy were predictors (11,12). In other studies, institutional delivery was 38.9% and influenced by focused antenatal care, multiple gestations, urban residence, and formal education of the women (13,14).…”
Section: Introductionmentioning
confidence: 92%